2020
DOI: 10.3389/fpls.2020.00345
|View full text |Cite
|
Sign up to set email alerts
|

The Pyruvate-Phosphate Dikinase (C4-SmPPDK) Gene From Suaeda monoica Enhances Photosynthesis, Carbon Assimilation, and Abiotic Stress Tolerance in a C3 Plant Under Elevated CO2 Conditions

Abstract: A pyruvate-phosphate dikinase (C 4 -PPDK) gene was cloned from Suaeda monoica, which had a single-cell C 4 photosynthesis pathway without Kranz anatomy and was functionally validated in a C 3 model plant under different abiotic stress conditions in an ambient and elevated CO 2 environment. Overexpression of SmPPDK promoted growth of C 3 transgenic plants, enhancing their photosynthesis (CO 2 assimilation) by lowering photorespiration under stress conditions. Transgenic plants also showed an improved physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…Modulation in the overall metabolome due to the developmental and environmental cues has previously been reported (Patel et al, 2020; Shekhar, Agrawal, et al, 2016). Even an overall reprogramming of the accumulation of primary and secondary metabolites due to the ectopic expression of a single gene has also been studied (Shekhar et al, 2016b; Yadav et al, 2020). The plant accumulates several organic acids, amino acids, polyamines and lipids, besides producing different metabolites in response to stress conditions (Guy et al, 2008; Sharma et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulation in the overall metabolome due to the developmental and environmental cues has previously been reported (Patel et al, 2020; Shekhar, Agrawal, et al, 2016). Even an overall reprogramming of the accumulation of primary and secondary metabolites due to the ectopic expression of a single gene has also been studied (Shekhar et al, 2016b; Yadav et al, 2020). The plant accumulates several organic acids, amino acids, polyamines and lipids, besides producing different metabolites in response to stress conditions (Guy et al, 2008; Sharma et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Total metabolites were extracted from selected transgenic and WT plants, and analysed by gas chromatography–mass spectrometry (Yadav et al, 2020). Briefly, fine powder of leaf samples (1 g) were made using liquid N 2 , and total metabolites were extracted with 100% ethanol (ice‐cold).…”
Section: Methodsmentioning
confidence: 99%
“…Engineering of photorespiratory bypasses, complete as well as partial, and modifications in other genes, such as phosphophenol pyruvate carboxylase (PEPC), cytochrome c 6 (Cyt c 6 ), and pyruvate phosphate dikinase (PPDK) have resulted in improved photosynthesis, as well as an enhancement in soluble sugars and starch ( Kebeish et al, 2007 ; Xia & Cao, 2013 ; Nölke et al, 2014 ; Dalal et al, 2015 ; Yadav et al, 2018 ; Yadav, Rathore & Mishra, 2020 ). Nölke et al (2014) have also reported an enhancement in sugar contents by transforming GDH alone in potato.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, plants modulate their several metabolic and physiological processes to cope with these conditions. Indeed, many stress-related genes were characterized from halophytes, and novel candidate genes are always welcomed, which provide endurance for a sustainable demand of agriculture [ 8 , 11 , 42 ]. In this study, a novel CSC1-like gene SbERD4 was isolated from a nutritionally and industrially important extreme halophyte Salicornia brachiata [ 43 , 44 , 45 , 46 ], and it was functionally characterized into Nicotiana tabacum cv.…”
Section: Discussionmentioning
confidence: 99%